Effectiveness of Neem Seed Extract Formulation (Azadirachta Indica) and Bitung (Barringtonia asiatica) against Mealybug Papaya (Paracoccus marginatus) (Hemiptera: Pseudococcidae) - Vinka Salsabilla; Sudarjat Sudarjat; Yani Maharani (CROPSAVER, 2022)
The papaya mealybug (Paracoccus marginatus) Williams & Granara de Wilink (Hemiptera: Pseudococcidae) is a main pest of papaya plants. Attacks by these pests can cause plants failed to produce the fruit and even to death. The usual control technique used by farmers is the use of synthetic pesticides that have a negative impact on human health and the environment. The alternative to control using botanical insecticides is a good solution to control the population of P. marginatus. The purpose of this study is to know the effect of neem seed oil formulation and bitung to know which treatments with concentrations are most effective in reducing the population density of papaya mealybug pests. The experiment took place in Rejasari Village, Langensari Subdistrict, Banjar City, West Java, from March 2021 to July 2021. Experiment using the Randomized Block Design consisted of ten treatments with three replications. The results were obtained that a formulation of bitung 3% could suppress the densities of papaya mealybug ( P. marginatus) populations at 65%. The average weight of the resulting papaya contained a 3% formulation of bitung found at 9.8 kg/tree. botanical pesticides of bitung oil 3% can be used instead of synthetic pesticides to control the population of P.marginatus.